The Effectiveness of Using Padlet and Slack Application in Teaching Writing - Kartika Rinanda; Rudi Hartono; Fahrur Rozi (Universitas Islam Negeri (UIN) Syekh Wasil, Kediri, Indonesia, 2024)
The purpose of this research is to assess the effectiveness of using Padlet and Slack application as collaborative tools in teaching writing to extrovert and introvert students. It also examines the differences in effectiveness both tools in teaching writing to students with different personalities. This research focuses on the effectiveness of using some tools in teaching, thus the use of experimental design with 2x2 factorial design will be conducted. The population of this study are the tenth grade students of SMAN 1 Tebing Tinggi. Two groups of students were used in this study and tested about their writing achievement before and after using Padlet and Slack application. Both classes also divided into extrovert and introvert students. In analyzing the data, the researcher used SPSS v.23 to conduct the normality test, homogeneity test and hypothesis test in answering the research questions. This research found that utilizing Padlet and Slack application is effective for teaching writing to extrovert and introvert students. The result of students’ pre-test between extrovert and introvert students was higher than students’ post-test, it indicated that there were significant effect of using Padlet and Slack application in teaching writing to extrovert and introvert students. Meanwhile, there were no differences and relationships between Padlet and Slack application in teaching writing to extrovert and introvert students, it showed that both Padlet and Slack application were effective to be collaborative tools in teaching writing because both collaborative tools can improve the students’ writing achievement.